Climate change events in the Bengali migration to the Chittagong Hill Tracts (CHT) in Bangladesh. (28th May 2021) - Islam, Rafiqul; Schech, Susanne; Saikia, Udoy
ABSTRACT: The internal migration of Bengali people to the CHT since the 1970s has been a significant factor in the long-standing ethnopolitical conflict in this region. The prevailing view is that while poverty and environmental disasters were push factors in this migration, government settlement programmes were primarily responsible for this population shift. This article offers a fresh perspective on this historic migration by exploring its environmental causes. It shows through an analysis of a questionnaire survey and interviews with Bengali settlers in the CHT that climatic events such as floods, cyclones, and riverbank erosion contributed to the migration decisions of the majority of the respondents. Government protection and provision of land and social networks in the CHT were mediating factors that enabled Bengali migrants to settle permanently in the CHT. This insight challenges the conventional narrative that the settlement was primarily politically motivated and confirms that complex migration motivations cannot be reduced to single drivers.